ANALISA PROFIL MUKA AIR BANJIR SUNGAI KRUENG PASE KABUPATEN ACEH UTARA - Ibrahim Ibrahim; Abdullah Irwansyah; Muhammad Reza (Politeknik Negeri Lhokseumawe, 2017)
Excess water capacity in river areas will cause flood hazards that mostly occur in downstream areas that are flood areas at high risk as a result of natural processes and the effects of human actions. In the case of floods, water runoff undermines the embankments and drowns agricultural / settlement areas upstream, and is aggravated by considerable sedimentation. Based on the existing problems, the analysis of the discharge and the water level (water profile) becomes very important to get a precise picture of locations prone to the overflow of the river Kr. This pase. Discharge and water profile analysis using HEC RAS software for various return periods. From the results of the research is expected to get a clear picture of the location that is vulnerable to overflow so that in handling the river will be on target. Based on the calculation using HEC RAS software, at point P 581 the water level condition at 2.3 years discharge the difference of the height of the embankment and the water level is 50 cm to 60 cm, while in the discharge condition 25 years the elevation of the face almost passes through the dike's height with a selisish of about 10 -15 cm. This condition is an unsafe category because for rivers whose debit is greater than 15 m3/s the minimum wavelength is 1.00 m. So that with good conditions at 2.3 years discharge and 25 years of discharge is very potential to occur overflow.Keywords: discharge, waterlevel, flood